The Effect of Rising Income Inequality on Taxation and Public Expenditures: Evidence from U.S. Municipalities and School Districts, 1970–2000 - Boustan, Leah; Ferreira, Fernando; Winkler, Hernan; Zolt, Eric M. (The Review of Economics and Statistics, 2013)
The income distribution in many developed countries widened dramatically from 1970 to 2000. Some scholars argue that income inequality contributes to a host of social ills by undermining voters' willingness to support public expenditures. In contrast, we find that growing income inequality is associated with an expansion in government revenues and expenditures on a wide range of services in U.S. municipalities and school districts. Results are robust to a number of model specifications, including instrumental variables that address the endogeneity of the local income distribution. Our results are inconsistent with models predicting that heterogeneous societies provide lower levels of public goods.